2019
DOI: 10.1097/aog.0000000000003404
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal Contraception and Vaginal Infections Among Couples Who Are Human Immunodeficiency Virus Serodiscordant in Lusaka, Zambia

Abstract: To examine the relationship between hormonal contraception and vaginal infections with bacterial vaginosis, vaginal candidiasis, or trichomoniasis. METHODS:Couples who were human immunodeficiency virus (HIV) serodiscordant in Zambia were enrolled in a longitudinal cohort study. From 1994 to 2002, both partners were seen quarterly and received physical exams including genital examinations. Separate rates for three outcome infections of interest (bacterial vaginosis, vaginal candidiasis, and trichomoniasis) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 72 publications
(68 reference statements)
1
9
0
Order By: Relevance
“…By utilizing the abundant glycogen, lactobacilli can produce enough lactic acid to create an acidic vaginal microenvironment, and thus protecting women from BV infection (Kalia et al, 2020; Wessels et al, 2018). Based on a meta‐analysis, Vodstrcil et al (2013) found that the use of hormonal contraceptives was highly relevant to a decreased incidence of prevalent BV, which is in accordance with the experimental result reported by Haddad et al (2019). Moreover, it was also reported that progesterone and estrogen act as modulators to regulate the human immune mechanisms in the genital tract, such as controlling the level of immunoglobulins and defensins (Faught & Reyes, 2019).…”
Section: The Pathogenesis Of Bvsupporting
confidence: 73%
“…By utilizing the abundant glycogen, lactobacilli can produce enough lactic acid to create an acidic vaginal microenvironment, and thus protecting women from BV infection (Kalia et al, 2020; Wessels et al, 2018). Based on a meta‐analysis, Vodstrcil et al (2013) found that the use of hormonal contraceptives was highly relevant to a decreased incidence of prevalent BV, which is in accordance with the experimental result reported by Haddad et al (2019). Moreover, it was also reported that progesterone and estrogen act as modulators to regulate the human immune mechanisms in the genital tract, such as controlling the level of immunoglobulins and defensins (Faught & Reyes, 2019).…”
Section: The Pathogenesis Of Bvsupporting
confidence: 73%
“…Studies which reported increased vaginal microbial diversity or lower levels of Lactobacillus in women using DMPA compared to other contraceptive groups were confounded by small sample sizes or were cross‐sectional in nature. The longitudinal studies and larger cross‐sectional studies by Dabee and Noel‐Romas et al indicate that differences in the vaginal microbiome with DMPA are mild and associated with a reduction in BV‐associated bacteria, as reported in previous meta‐analyses 8,38 . An important observation, discussed in the Noel‐Romas et al paper, is the influence of the microbiome in the context of examining DMPA‐associated inflammation making it an important consideration.…”
Section: Dmpa Use and The Composition Of The Vaginal Microbiomementioning
confidence: 88%
“…For example, a meta‐analysis by Vodstrcil et al which focused on studies published before January 2013 reported a decreased incidence of BV, defined by Nugent or Amsel scores, with the use of both progestin‐based contraceptives and combined hormonal contraceptives 8 . A more recent review by Haddad et al noted similar observations 38 . Recently, six publications evaluated the vaginal microbiome with DMPA use.…”
Section: Dmpa Use and The Composition Of The Vaginal Microbiomementioning
confidence: 96%
See 2 more Smart Citations